Dural Infantile Hemangioma Masquerading as a Skull Vault Lesion - Philpott, C.; Wray, A.; MacGregor, D.; Coleman, L. (American Journal of Neuroradiology, 2012)
SUMMARY: We describe a case of intracranial dural IH initially diagnosed as a primary skull vault lesion hemangioma due to associated focal hyperostosis. Histopathologic examination of the dural component confirmed IH. The case is discussed in the context of IH within the neural axis. Glut-1glucose transporter-1 by immunohistochemistryIHinfantile hemangioma